STATUS OF WOMEN WHO HAVE BEEN SUBJECTED TO EARLY MARRIAGE: A STUDY CONDUCTED IN MALAPPURAM DISTRICT - Linshi.P (International Contemporary Research Journal in Management and Social Science, 2015)
tKerala state shows high development indices among the other states in India. Women’s political participation, work participation, violence against women etc. show that the status of women in Kerala is not as glowing as it is projected in official documents. Early marriages are still taking place in Kerala, especially in the rural areas. The present study has taken respondents from Malappuram district of Kerala. Semi-structured interview was the tool for data collection. Study objectives are; understand the socio –economic and cultural factors leading to Early Marriage, study the social and emotional issues of early married women and analyse early married women’s perception about early marriage. The study analyzed the status of early married Women with feminist research methods.